115k views
3 votes
6*7-3^2*9+4^3
SHOW UR work

2 Answers

5 votes

6x7-3 ^2 x 9+4 ^3

6x7- 9 x 9+64

42- 9 x 9+64

42- 81 +64

-39 + 64 = 25

Just follow the rules of P.E.M.D.A.S.

P= Parenthesis

E= Exponents

M= Multiply

D= Divide

A= Add

S = Subtract

User Akahunahi
by
5.6k points
7 votes

Use PEMDAS

P Parentheses first

E Exponents (ie Powers and Square Roots, etc.)

MD Multiplication and Division (left-to-right)

AS Addition and Subtraction (left-to-right)


6\cdot7-3^2\cdot9+4^3\\\\step\ 1:\\6\cdot7=42\\3^2=3\cdot3=9\\4^3=4\cdot4\cdot4=64\\\\=42-9\cdot9+64\\\\step\ 2:\\9\cdot9=81\\\\=42-81+64\\\\step\ 3:\\\text{use commutative property}\ a+b=b+a\\\\=42+64-81\\\\step\ 4:\\\text{make the sum and the difference}\\\\=106-81=25\\\\Answer:\ \boxed{25}


User David Hansen
by
5.1k points